'A strong curatorial vision for the neighbourhood': Countering the diplomatic condition of the arts in urban neighbourhoods. Issue 1 (1st September 2017) - Graham, Janna
It is by now common knowledge that the arts are complicit in projects of urban redevelopment, dispossession and gentrification. Where accounts of this process in the United States and the United Kingdom have often focused on artists' occupations of studios and gallery spaces in low-income areas, or on the public art commissioning process, more recent trends extend the artists' role in gentrification more directly. Artists are now commissioned to engage in community visioning and engagement activities, efforts to naturalize the development narrative, and art projects that support the policing of bodies seen to be unruly or undesirable to the process of gentrification (itself re-branded as 'regeneration'). This article looks at the multifaceted role that artists and arts organizations play in the development and dispossession process, describing them as having produced a 'diplomatic condition', in which artists and arts organizations are used to massage and assuage conflicts, while a systematic war is waged on poor and working-class communities. Far from innocent, artists and arts organizations have increasingly been called upon to leave the comfort of what Tariq Ali describes as the 'extreme centre' to more actively take sides. This article draws from a situated ethnography of my work at the Centre for Possible Studies, an arts and research space in London's Edgware Road neighbourhood, and readings from a number of recent struggles aligning artists and residents differently, including Los Angeles' Boyle Heights Community, and the Southwark Notes Campaign in London's Elephant and Castle Community. It questions what role artists and arts organizations could play to counter such a diplomatic condition.